Shared Medical Appointments May Be Effective for Improving Clinical and Behavioral Outcomes in Type 2 Diabetes: A Narrative Review - Menon, Kirthi; Mousa, Aya; de Courten, Maximilian PJ; Soldatos, Georgia; Egger, Garry; de Courten, Barbora (Frontiers in Endocrinology, 2017)
Type 2 diabetes mellitus (T2DM) is a complex chronic disease affecting over 400 million people worldwide. Managing T2DM and its associated complications in individual patient consultations poses substantial challenges to physicians due to limited time and resources, and lack of access to multidisciplinary teams. Shared medical appointments (SMAs) are consecutive medical consultations provided by a physician in a group setting, where integrated medical care and patient education are delivered in a single session. SMAs allow physicians to deliver the same level of care to multiple patients at the same time, thereby maximizing available resources. However, the effectiveness and practicality of SMAs in the management of T2DM remains unknown. This narrative review summarizes current and emerging evidence regarding the effectiveness of SMAs in improving clinical outcomes in patients with T2DM, as well as whether SMAs are associated with reduced costs and improved diabetes-related behavioral and lifestyle changes. An extensive literature search was conducted on major electronic databases including PubMed and Google Scholar using keywords including SMAs, group visits, and T2DM to identify all studies of SMAs in patients with T2DM. Studies in type 1 diabetes or mixed or unspecified populations were excluded, as well as studies where SMAs did not involve a physician since these do not meet the classical definition of a SMA. Nineteen studies were identified and are included in this review. Overall, current evidence suggests that SMAs delivered regularly over time may be effective in improving glycemic outcomes, diabetes knowledge, and some diabetes-related behaviors. However, the main limitation of existing studies was the paucity of comparisons with standard care which limits the ability to draw conclusions regarding whether SMAs are superior to standard care in T2DM management. Moreover, the small number of studies and substantial heterogeneity in study designs, populations, and interventions creates difficulties in establishing the practicality and efficiency of SMAs in the clinical care setting. We conclude that there remains a need for larger studies to identify populations who may or may not benefit from the SMA model of care, and to clarify the potential benefits and barriers to implementing SMAs into routine diabetes care.